If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3 = x + s Reorder the terms: -3 + 2x = x + s Reorder the terms: -3 + 2x = s + x Solving -3 + 2x = s + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -3 + 2x + -1x = s + x + -1x Combine like terms: 2x + -1x = 1x -3 + 1x = s + x + -1x Combine like terms: x + -1x = 0 -3 + 1x = s + 0 -3 + 1x = s Add '3' to each side of the equation. -3 + 3 + 1x = 3 + s Combine like terms: -3 + 3 = 0 0 + 1x = 3 + s 1x = 3 + s Divide each side by '1'. x = 3 + s Simplifying x = 3 + s
| x^2-8+11=0 | | 9x^2+6x=3x+6 | | 11(9x+2)=-2(3x-11) | | 3(-5b(2/3))=2-7b | | 9s-3=10+4(s+8) | | x-6+9=1 | | 7w-8=1+10(w+4) | | -3x+4=-10+5(-7-x) | | 8m-5+m=67 | | x-6+3=9 | | -1=4+2(1-5x) | | 22=5x-7 | | X^2-17x=-30 | | 42=81 | | 24x^2=x^6 | | -2+3(1+2x)=-2x+3 | | 5g-2x=9 | | (-2)(1+6m)=-10+8(10+2m) | | 4(x+5)=10x+5 | | 6v^2-4v-11=-6 | | Y^2-12y=160 | | 0=6-3(5+2x) | | 5p+7=4p+13 | | -3.61=3p+7.7 | | F(x)=2ln(x+3) | | -1+8(7-6x)=2x+6 | | 5g-2x=a | | 3L+12=2L+6L+1 | | 4(a+8)+9=12a-9 | | 9=5-4(2x-5) | | 2(k+1)+9=8k-11 | | 10+9(-10-9x)=8-x |